Restricción del Procedimiento Abreviado con el fin de evitar que los Procesados Reincidentes se beneficien de este Procedimiento Especial - Tulcanaza Cartuche, Carla Alejandra (2023)
This Curricular Integration Work entitled "Restriction to the abbreviated procedure in order to prevent recidivist defendants from benefiting from this special procedure", has been of interest for its development given that the high rates of recidivism in Ecuador because many defendants who incur in a criminal offense for several times have benefits from the abbreviated procedure creating a modus vivendis of entries and exits from the Social Rehabilitation Centers. In the investigation that has been carried out by means of thirty surveys and five interviews with legal professionals, they say, there is an abuse on the part of recidivist defendants when accessing the abbreviated procedure and how this special procedure, apart from being considered for justice as a means to save time and shorten the criminal process, also became the means of entry and exit in a short time for habitual offenders, who relapse in committing crimes based on their way of life. The results of the application of surveys and interviews, they have allowed me to verify the objectives set out in this research, both general and specific, and therefore they have allowed me to propose the reform project to the Organic Integral Penal Code in order to incorporate an additional numeral to Article 635 that stipulates the rules of the abbreviated procedure, to restrict access to this special procedure in the case of recidivist offenders.